Effect of salinity on the physiological growth and proximate mineral content of purslane (Portulaca Oleracea L.) - Tatiana Imrah Roslan (2016)
Effect of salinity on the physiological growth and proximate mineral content of purslane (Portulaca Oleracea L.) "The demand for salinity-tolerant plant is increasing due to augmented use of effluent or low-quality water irrigation and the growing Purslane in coastal areas. Purslane (Portulaca oleracea) is a drought and salt tolerant annual plant which contains high amounts of beneficial antioxidant vitamins and minerals. This study is to determine the effects of different concentrations of sea water application on the physiological growth and proximate mineral contents on this succulent weeds. The experiment was conducted in pots filled with a mixture of top soil in the rain shelter at the Faculty of Sustainable Agriculture, UMS (Sandakan campus). The planting medium is top soil and the weeds were subjected to six different sea water treatments. The electrical conductivity (EC) of collected sea water was 45.3dSm-1 then diluted according to a different level of salinity which is 0.0 (tap water), 4.53, 9.06, 13.59, 18.12 and 22.65 dSm-1• Each treatment was replicated five times using Completely Randomized Design (CRD) and the treatment means were compared by Least Significance Differences (LSD) at 5% probability level. The physiological changes were evaluated to indicate the current condition of Purslane plant every week (for three weeks) after initial sea water application, and at the end of the evaluation week the whole plants were harvested. The result obtained showed Purslane response varied to different levels of salinity, and the growth of Purslane was more suppressed under 50% of salinity level (22.65 dSm-1). The physiological changes were also evaluated to indicate the current condition of Purslane plant every week (for three weeks) after initial sea water application and at the end of the evaluation week the whole plants were harvested. The morphological traits suppressed highest at 50% of salinity level, stem diameter reduction was (79.7%); leaf width reduction was (66.1%); leaf length reduction was (54.5%). The highest mineral residue content was found in leaves and the mineral composition was also affected by the salinity level. Nitrogen and crude protein content reduced with the increasing of salinity treatment. At 50% of salinity level (22.65 dSm-1 ) the nitrogen content was (1.05%) and showed the highest reduction (35.1%) compared to other treatments. At the same salinity treatment crude protein content showed the lowest value (6.62%) and at the same time it showed the highest total reduction (34.7%) compared to other treatment. The findings suggested that Purslane can be utilized at salt-effected soil and helps reduce the salt element in soil. This plant can become an alternative for a healthy lifestyle due to its good antioxidant and Omega-3 content. In addition, Purslane has the potential to become a key vegetable crop, especially for functional food and nutraceutical applications. The antioxidant content and nutritional value of purslane are important for human consumption and the potential use of this herb for the future is very promising.